Seconds-Resolved, In Situ Measurements of Plasma Phenylalanine Disposition Kinetics in Living Rats - Idili, Andrea; Gerson, Julian; Kippin, Tod; Plaxco, Kevin W (Analytical chemistry (Washington), 2021)
Current knowledge of the disposition kinetics of endogenous metabolites is founded almost entirely on poorly time-resolved experiments in which samples are removed from the body for later, benchtop analysis. Here, in contrast, we describe real-time, seconds-resolved measurements of plasma phenylalanine collected in situ in the body via electrochemical aptamer-based (EAB) sensors, a platform technology that is independent of the reactivity of its targets and thus is generalizable to many. Specifically, using indwelling EAB sensors, we have monitored plasma phenylalanine in live rats with a few micromolar precision and a 12 s temporal resolution, identifying a large-amplitude, few-seconds phase in the animals’ metabolic response that had not previously been reported. Using the hundreds of individual measurements that the approach provides from each animal, we also identify inter-subject variability, including statistically significant differences associated with the feeding status. These results highlight the power of in vivo EAB measurements, an advancement that could dramatically impact our understanding of physiology and provide a valuable new tool for the monitoring and treatment of metabolic disorders.